1995
DOI: 10.1074/jbc.270.43.25992
|View full text |Cite
|
Sign up to set email alerts
|

Pigment Epithelium-derived Factor Behaves Like a Noninhibitory Serpin

Abstract: Pigment epithelium-derived factor (PEDF), a neuritepromoting factor, has an amino acid primary structure that is related to members of the serine protease inhibitor (serpin) family. Controlled proteolysis of native PEDF (50 kDa) with either trypsin, chymotrypsin, elastase, or subtilisin yields in each case one major limited product of 46 kDa as analyzed by SDS-polyacrylamide gel electrophoresis. N-terminal sequence analysis of the isolated 46-kDa products indicates a favored cleavage region located toward the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
119
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 199 publications
(127 citation statements)
references
References 35 publications
1
119
0
Order By: Relevance
“…However, PEDF has no known protease target for inhibition, and furthermore, its neurotrophic activity is determined by sequences away from its serpin-exposed loop, the structural determinant of serpin protease inhibition (25). The present study indicates that PEDF can interact with cells derived from the retina and the central nervous system.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…However, PEDF has no known protease target for inhibition, and furthermore, its neurotrophic activity is determined by sequences away from its serpin-exposed loop, the structural determinant of serpin protease inhibition (25). The present study indicates that PEDF can interact with cells derived from the retina and the central nervous system.…”
Section: Discussionmentioning
confidence: 89%
“…Given these studies, we had previously attempted to determine the inhibitory capacity of PEDF against serine proteases. First, an inhibitory activity against proteases, among others thrombin, could not be demonstrated for PEDF (24,25). Second, PEDF, like the noninhibitory serpins ovalbumin, angiotensinogen, and maspin, lacks the serpin S 3 R conformational change upon cleavage of its serpin-exposed loop (25,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PEDF is a 50-kDa glycoprotein and a member of the serpin superfamily without a demonstrable inhibitory activity against serine proteases (23). It has been shown that the biological activities of PEDF depend on binding to cell surfaces of target cells rather than inhibiting serine protease.…”
mentioning
confidence: 99%
“…Pigment epithelium-derived factor (PEDF), a 418-aa 50-kDa glycoprotein, is a member of the serine protease inhibitor (serpin) family (10,11). Although PEDF has a putative proteasesensitive loop, unlike classical serpins such as ␣1-antichymotrypsin (ACT), PEDF lacks protease inhibitory activity.…”
mentioning
confidence: 99%